Molecular mechanisms and tissue targets of brominated flame retardants, BDE-47 and TBBPA, in embryo-larval life stages of zebrafish (Danio rerio) - Parsons, Aoife; Lange, Anke; Hutchinson, Thomas H.; Miyagawa, Shinichi; Iguchi, Taisen; Kudoh, Tetsuhiro; Tyler, Charles R. (Aquatic toxicology, 2019)
•Zebrafish thyroid system is vulnerable to disruption by BFRs during early development.•BFRs disrupt thyroid axis of zebrafish embryo-larvae at multiple mRNA transcripts.•Effects of BFRs on the thyroid system are tissue- and developmental stage-specific.•Implications of transcriptional changes targets involved in tissue development. Brominated flame retardants are known to disrupt thyroid hormone (TH) homeostasis in several vertebrate species, but the molecular mechanisms underlying this process and their effects on TH-sensitive tissues during the stages of early development are not well characterised. In this study, we exposed zebrafish (Danio rerio) embryo-larvae to 2,2′,4,4′-tetrabromodiphenyl ether (BDE-47) and tetrabromobisphenol A (TBBPA) via the water for 96 h from fertilisation and assessed for lethality, effects on development and on the expression of a suite of genes in the hypothalamic-pituitary-thyroid (HPT) axis via both real time quantitative PCR (qRT-PCR) on whole body extracts and whole mount in situ hybridisation (WISH) to identify tissue targets. The 96-h lethal median concentration (96h-LC50) for TBBPA was 0.9 μM and mortality was preceded by retardation of development (smaller animals) and morphological deformities including, oedemas in the pericardial region and tail, small heads, swollen yolk sac extension. Exposure to BDE-47 did not affect zebrafish embryo-larvae survival at any of the concentrations tested (1–100 μM) but caused yolk sac and craniofacial deformities, a curved spine and shorter tail at the highest exposure concentration. TBBPA exposure resulted in higher levels of mRNAs for genes encoding deiodinases (dio1), transport proteins (ttr), the thyroid follicle synthesis protein paired box 8 (pax8) and glucuronidation enzymes (ugt1ab) and lower levels of dio3b mRNAs in whole body extracts, with responses varying with developmental stage. BDE-47 exposure resulted in higher levels of thrb, dio1, dio2, pax8 and ugt1ab mRNAs and lower levels of ttr mRNAs in whole body extracts. TBBPA and BDE-47 therefore appear to disrupt the TH system at multiple levels, increasing TH conjugation and clearance, disrupting thyroid follicle development and altering TH transport. Compensatory responses in TH production/ metabolism by deiodinases were also evident. WISH analyses further revealed that both TBBPA and BDE-47 caused tissue-specific changes in thyroid receptor and deiodinase enzyme expression, with the brain, liver, pronephric ducts and craniofacial tissues appearing particularly responsive to altered TH signalling. Given the important role of TRs in mediating the actions of THs during key developmental processes and deiodinases in the control of peripheral TH levels, these transcriptional alterations may have implications for TH sensitive target genes involved in brain and skeletal development. These findings further highlight the potential vulnerability of the thyroid system to disruption by BFRs during early developmental windows.